2022
DOI: 10.1088/1755-1315/1034/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Land Use Cover Changes Over 29 Years in Papua Province of Indonesia Using Remote Sensing Data

Abstract: Land use/cover change (LUCC) observation and determination have been extensively discussed in natural resources management, biodiversity and ecosystem preservation, land management also climate changes studies. An evaluation of the LUCC in Merauke, the easternmost city of Indonesia, was conducted to gain relevant information in agriculture and forestry based on historical data from remotely sensed land cover data. To obtain the historical dynamics of the LUCC, a supervised classification algorithm was implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Notably, the resolution of the imagery for each year was 30 m by 30 m, with medium accuracy with sufficient bands. Therefore, to accurately classify the land use of remote sensing images, a supervised classification technique was employed [34][35][36]. The present study adopted the Chinese land use classification system developed by Liu Jiyuan to categorize the land use types based on the natural conditions and characteristics of the site.…”
Section: Classification Of Land Use Types and Testingmentioning
confidence: 99%
“…Notably, the resolution of the imagery for each year was 30 m by 30 m, with medium accuracy with sufficient bands. Therefore, to accurately classify the land use of remote sensing images, a supervised classification technique was employed [34][35][36]. The present study adopted the Chinese land use classification system developed by Liu Jiyuan to categorize the land use types based on the natural conditions and characteristics of the site.…”
Section: Classification Of Land Use Types and Testingmentioning
confidence: 99%
“…Precise land cover classification data play a vital role in regional development, such as natural resource management [1] and agricultural planning [2]. Numerous land classification tasks have relied on conventional optical imagery [3].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple examples of accurate plant height estimates using UAV imagery have been shown in crops such as barley ( Hordeum vulgare L.) (Bendig et al ., 2014; Herzig et al ., 2021), cabbage ( Brassica oleracea var. capitata L.) (Moeckel et al ., 2018), cotton ( Gossypium hirsutum L.) (Feng et al ., 2019; Liu et al ., 2020), eggplant ( Solanum melongena L.) (Moeckel et al ., 2018), faba bean ( Vicia faba L.) (Ji et al ., 2022), maize (Anthony et al ., 2014; Geipel et al ., 2014; Grenzdörffer, 2014; Su et al ., 2019; Varela et al ., 2017; Anderson et al ., 2019; Malambo et al ., 2018; Shi et al ., 2016; Tirado et al ., 2020; Adak, Murray, Božinović, et al ., 2021; Letsoin et al ., 2023), potato ( Solanum tuberosum L.) (de Jesus Colwell et al ., 2021; Xie et al ., 2022; Njane et al ., 2023), rapeseed ( Brassica napus L.) (Xie et al ., 2021), sorghum ( Sorghum bicolor L.) (Chang et al ., 2017; Shi et al ., 2016; Watanabe et al ., 2017; Gano et al ., 2021), soybean ( Glycine max L.) (Li et al ., 2022), tomato ( Solanum lycopersicum L.) (Moeckel et al ., 2018), and wheat ( Triticum aestivum L.) (Holman et al ., 2016; Madec et al ., 2017; Michalski et al ., 2018; Volpato et al ., 2021). Studies on plant height using UAVs have shown variable levels of success when compared to manual measurements due to plant structure, field layout, and improvements in best practices as more research was completed (Holman et al ., 2016; Sweet et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%